Perspectives of People with Dementia : Research Methods and Motivations. - Wilkinson, Heather (Jessica Kingsley Publishers, 2001)
People with dementia have often played a passive role in the investigation of their condition. The contributors to this book look at ways of redressing the balance and involving them in the research process. They describe the skills that researchers and care staff need when seeking to validate the views of people with dementia successfully.